2010
DOI: 10.1140/epjc/s10052-010-1281-y
|View full text |Cite
|
Sign up to set email alerts
|

The energy dependence of the hard exclusive diffractive processes in pQCD as the function of momentum transfer

Abstract: We predict the dependence on energy of photo(electro) production processes: γ(γ * )+ p → V + X with large rapidity gap at small x and large momentum −t transferred to V in pQCD. Here V is a heavy quarkonium (J/ψ, Υ) or longitudinally polarized light vector meson (in the electroproduction processes), etc. In the kinematics of HERA we calculate the dependence on energy of cross sections of these processes as the function of momentum transfer t, photon virtuality Q 2 and/or quarkonium mass. In the kinematical reg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…In the case of elastic photoproduction of J/ψ, α IP ≈ 1.2 for forward scattering and α IP ≈ 1 for −t ≈ m 2 J/ψ . Such a behavior is natural for the pQCD regime where double logarithmic terms are relevant for the interrelation between the t and s dependences [33].…”
Section: Experimental Evidence For the Pomeron Trajectorymentioning
confidence: 98%
See 1 more Smart Citation
“…In the case of elastic photoproduction of J/ψ, α IP ≈ 1.2 for forward scattering and α IP ≈ 1 for −t ≈ m 2 J/ψ . Such a behavior is natural for the pQCD regime where double logarithmic terms are relevant for the interrelation between the t and s dependences [33].…”
Section: Experimental Evidence For the Pomeron Trajectorymentioning
confidence: 98%
“…A further complication is that the QCD factorization theorem [56] was derived in the limit of t = const, x = const, and Q 2 → ∞. Recent studies [33] found that the pattern of the QCD evolution changes in the kinematical domain when −t becomes comparable to the intrinsic hardness scale of the process (Q 2 eff ∼ 3 GeV 2 for J/ψ photoproduction). The DGLAP equations require modifications in this case.…”
Section: Onset Of New Regime At Large Tmentioning
confidence: 99%